2015
DOI: 10.1016/j.dsr2.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Trailing edges projected to move faster than leading edges for large pelagic fish habitats under climate change

Abstract: Trailing edges projected to move faster than leading edges for large pelagic fish habitats under climate change, Deep-Sea Research II, http://dx. doi.org/10. 1016/j.dsr2.2014.04.007 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 71 publications
3
45
0
Order By: Relevance
“…The velocity of the poleward distribution shift reported here for the period 1998-2013, based on empirical observations and multiple environmental factors, is considerably faster than predictions made for similar mobile pelagic predators using modelled climate scenarios ranging from 2030 to 2100 (Hobday, 2010;Robinson et al, 2014). Suitable habitat is shifting south at a mean rate of 88.2 km decade À1 , independent of considerable variation observed due to season and ENSO.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The velocity of the poleward distribution shift reported here for the period 1998-2013, based on empirical observations and multiple environmental factors, is considerably faster than predictions made for similar mobile pelagic predators using modelled climate scenarios ranging from 2030 to 2100 (Hobday, 2010;Robinson et al, 2014). Suitable habitat is shifting south at a mean rate of 88.2 km decade À1 , independent of considerable variation observed due to season and ENSO.…”
Section: Discussionmentioning
confidence: 49%
“…Despite their widespread distributions, mobile pelagic predators have declined in abundance due to overfishing (Baum & Worm, 2009), causing changes to open ocean food webs (Myers et al, 2007;Worm & Tittensor, 2011). Climate-induced distribution shifts are likely to alter the functioning of pelagic ecosystems already under pressure from anthropogenic stressors (Hsieh et al, 2006;Beaugrand et al, 2008;Hazen et al, 2012;Robinson et al, 2014). Furthermore, mobile pelagic predators represent 20% of total economic value in global marine capture fisheries (FAO, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Current climate change predictions indicate that low oxygen zones will increase in size, which may lead to further habitat compression and thus increased vulnerability of these species. Additionally, species ranges may shift as a result of predicted ocean warming [144].…”
Section: Biophysical Interactionsmentioning
confidence: 99%
“…For example, Dueri et al (2014) predicted an expansion of unsuitable habitat for SKJ in the equatorial Pacific under climate change, with surface temperatures of N31°C considered unsuitable. Robinson et al (2014) assumed a thermal maximum for SKJ of 30°C, and also showed poleward shifts in habitat suitability off southeastern Australia. In contrast, results from this study suggest a general expansion of habitat for SKJ in the GoM and CBN.…”
Section: Discussionmentioning
confidence: 99%